The Problems of Patent Protection Related to Digital Assets in the Metaverse - Suppakijjumnong, Thanaporn (CMU Journal of Law and Social Sciences, 2024)
System architecture and appearance designs of digital assets in the metaverse are created with the creativity and innovative ideas of the creator that according to the objective of patent protection. However, the nature of these digital assets is kept in the form of an electronic data unit that is intangible; cannot be touched and seen with the naked eye whereas, the Thai patent law protects an invention and design of a physical product. The purpose of this article is to analyze problems related to patenting digital assets in the metaverse. It begins with studying technical information of digital assets in the metaverse, theories, doctrines, patent law, and other related laws of Thailand, International laws, the United States, the European Union, the People's Republic of China (China) and the Republic of China (Taiwan). The study found that the definition of “invention” and “process” under Section 3 of the Patent Act B.E. 2522 may be incomprehensive to intangible products or virtual products that are part of digital assets in the metaverse, whereas the process that is not abstract ideas should be protected. The product character of the invention patent must direct to a product as a legal thing: a corporeal object, different from a product design that a product could be meaning to a property. In terms of “design” is not clear whether the digital design and the digital assets are included or classified in a patent for the design. However, if there is a transformation from a physical product to an appearance of digital asset, it could be deemed as “new” under Section 56 despite its lack of original and conflict with the truth that it only transfers the appearance to a different type of product. This study proposes to revise the Patent Act B.E. 2522 to be more comprehensive to include the specific technical solutions of a process that is not direct to a result of a core functionality of the physical product. To give a new definition to “design” to include a digital design and to propose other appropriate revising to cater for new technology development especially, in digital assets in the metaverse.